I was looking over my notes for centre of mass for a system and it says:(adsbygoogle = window.adsbygoogle || []).push({});

[tex] c = \frac {1} {M} \sum_{i} m_i\ddot{r}_i = \sum_{i}(E_i + \sum_{j \neq i}F_i_j) [/tex]

where M is the total mass of the system.

Then it considers the centre of Mass in motion:

[tex] M \ddot{c} = \sum_i m_i \ddot{r}_i = \sum_{i}(E_i + \sum_{j \neq i}F_i_j) [/tex]

[tex] = \sum_{i}E_i + \sum_{j \neq i}F_i_j = E + \sum_{i < j}(F_j_i + F_j_j)[/tex]

[tex] = E [/tex]

The thing is, I don't understand the line:

[tex]E + \sum_{i < j}(F_j_i + F_j_j)[/tex]

and how it comes about (especially the i < j) part.

Any help would be grateful!

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Homework Help: Centre of mass

**Physics Forums | Science Articles, Homework Help, Discussion**